Effect of nonsteroidal antiinflammatory drugs NSAIDs, analgesics and coxibs on the magnitude and rate of orthodontic tooth movement - Chumpitaz Cerrate, Víctor Manuel Manuel (2014)
The objective of this study was to determine the effects of diclofenac, etoricoxib, ibuprofen and paracetamol on the magnitude of orthodontic tooth movement. 50 Holtzman rats participated in 5 groups of 10 rats each. At the beginning of study the distance between the angles inciso-distals of both maxillary incisive was measured in each animal, using a caliper, and immediately an orthodontic device with a reciprocal action force of 35 g. was adhered to them. Each group received different treatments intraperitoneally (A: NaCl, control group, B: diclofenac, C: etoricoxib, D: ibuprofen, E: paracetamol) for 5 days. In all controls made the 1st, 3rd, 5th and 7th days, interincisive distance was significantly lower in the ibuprofen and diclofenac groups, without significant difference in the etoricoxib and paracetamol groups; all compared with control group. It was shown that administration of ibuprofen and diclofenac significantly diminish the magnitude of orthodontic tooth movement in rats. It was demonstrated that administration of paracetamol and etoricoxib not significantly decrease the magnitude of orthodontic tooth movement in rats.